2021
DOI: 10.1186/s12877-021-02010-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk‐of‐falling related outcomes improved in community‐dwelling older adults after a 6-week sideways walking intervention: a feasibility and pilot study

Abstract: Background Aging increases fall risk and alters gait mechanics and control. Our previous work has identified sideways walking as a potential training regimen to decrease fall risk by improving frontal plane control in older adults’ gait. The purposes of this pilot study were to test the feasibility of sideways walking as an exercise intervention and to explore its preliminary effects on risk-of-falling related outcomes. Methods We conducted a 6-wee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 95 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…In our study, improvement was observed in the aspects of functional autonomy and lower limb strength. In a pilot intervention study, performed through lateral walking for 6 weeks, it was possible to observe an improvement in walking speed and a reduction in the risk of falls in community-dwelling older people aged 65 years or older [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, improvement was observed in the aspects of functional autonomy and lower limb strength. In a pilot intervention study, performed through lateral walking for 6 weeks, it was possible to observe an improvement in walking speed and a reduction in the risk of falls in community-dwelling older people aged 65 years or older [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…More than half of all falls occur while performing common daily activities such as walking, arising from chair, or transferring [ 5 , 6 ]. Other factors such as advancing age, multimorbidity, vision and hearing impairment, gait and balance impairment are also reported to increase the risk of fall in older adults [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobility and physical function impairments, often operationalized as spatiotemporal gait parameters, are strongly associated with concerns about falling. A decrease in gait speed is frequently used as a predictor of fall risk and disability and a marker of frailty because it correlates with functional loss and imminent death 36,37 . Therefore, spatiotemporal gait parameters are a major factor in uencing mobility and physical function, and they are meaningful biomechanical assessments for monitoring the effects of exercise programs in older adults.…”
Section: Discussionmentioning
confidence: 99%